Antibiotics- and Heavy Metals-Based Titanium Alloy Surface Modifications for Local Prosthetic Joint Infections - Jaime Esteban; María Vallet-Regí; John J. Aguilera-Correa (MDPI AG, 2021)
Prosthetic joint infection (PJI) is the second most common cause of arthroplasty failure. Though infrequent, it is one of the most devastating complications since it is associated with great personal cost for the patient and a high economic burden for health systems. Due to the high number of patients that will eventually receive a prosthesis, PJI incidence is increasing exponentially. As these infections are provoked by microorganisms, mainly bacteria, and as such can develop a biofilm, which is in turn resistant to both antibiotics and the immune system, prevention is the ideal approach. However, conventional preventative strategies seem to have reached their limit. Novel prevention strategies fall within two broad categories: (1) antibiotic- and (2) heavy metal-based surface modifications of titanium alloy prostheses. This review examines research on the most relevant titanium alloy surface modifications that use antibiotics to locally prevent primary PJI.